(3eNJUQ cJGH GdYjfs - (3eMeO Hf GdMSf Hf YHjO Gddg Hf ePML GdRHjOj GdCfOdSj GdETHjdj, CHh HcQ , J (B379 (3g` s; (3CHh eMeO YHO GdZfj Hf SYjO GdMGaX, GdGROj GdeUQj,J (B409 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkGjHdZ QVGg hjhLH GdRdbi dOjg gPG cJGH CeQ HLeYg hJCdjag CejQ GdeDefjf GdMce GdeSJfUQ HGddg HGH GdKfGFi GdeVYa GdUMjM s
(3BNQgG (B:s
(3jfJgi HMQa GdjGA , HGH GdKfGFi GdeVGYa GdeYJd hBNQ eG ajg (B: (3geRhG cQGgjI GJUGd GdhGeGJ GdjGAGJ Je eNJUQ GdYjf ef GdfSNI GdcHQi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI Ydi Qb ZRGd s
(3YfhGfGJ GdCHhGH ecJHhI HGdNW Gdchai GdePgH HghGeT GdfSNI JYdjbGJ HNW GdfGSN efbhdI ef fSNI GdYdGeI GHf GdSjO GdHWdjhSi GdefbhdI ef fSNI GdMce GdeSJfUQ HGddg GdJi gi HNW GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GddZIs